ASSOCIATION BETWEEN SPECIFIC FEATURES OF GATA3 TRANSCRIPTION FACTOR EXPRESSION AND LYMPH NODE METASTASIS IN LUMINAL BREAST CANCER - S. V. Vtorushin; D. V. Vasilchenko; К. Y. Khristenko; N. V. Krakhmal; I. V. Stepanov; М. V. Zavyalova; E. M. Slonimskaya; S. V. Patalyak (Сибирский онкологический журнал, 2017)
Currently, the study of the markers of cell differentiation, proliferative regulators, and molecules involved in the development of drug resistance mechanisms in breast cancer is extremely important. The transcription factor GATA3 plays an essential role in the differentiation and proliferative activity of luminal breast cancer cells, being a tumor suppressor. The GATA3 positive expression is most frequently observed in invasive carcinoma of no special type. High expression of GATA3 is associated with low-grade ER-positive cancer with a favorable prognosis. Low GATA3 expression is observed in patients with high-grade and hormone receptor-negative cancer. The study of GATA3 expression is necessary for understanding the development of drug resistance mechanisms and developing approaches to overcome them as well as for determining the response to hormone therapy. Aim. The present study was undertaken to study the expression characteristics of the transcription factor GATA3 in patients with luminal breast cancer and to evaluate their relationship with the parameters of lymphogenous metastasis. Material and methods. The study included 64 patients with stage T1–4N1–3M0 invasive breast cancer. The primary tumor tissue and all removed lymph nodes were morphologically examined. The diagnosis was established according to the WHO criteria (2012). Results. Low GATA3 expression was associated with a high risk of lymph node metastases, while high GATA3 expression was associated with the absence of lymph node metastases. Heterogeneous GATA3 expression was associated with high risk of lymph node metastasis, and as a consequence, with poor prognosis. Conclusion. The relationship between the expression of GATA3 protein and lymphogenic metastasis in patients with luminal breast cancer was found.